Impact of Whistleblowing System Between the Vousinas Fraud Hexagon Theory and Financial Statement Fraud - Muhammad Rafi Raihan; Imang Dapit Pamungkas; Yulita Setiawanta; Enny Susilowati Mardjono (Universitas Muhammadiyah Semarang, 2024)
This study examines and analyses the impact of pressure, opportunity, rationalization, capability, ego, and collusion on financial statement fraud. Testing of the whistleblowing system variable is a moderating variable in the relationship between the fraud hexagon theory variable and financial statement fraud. Purposive sampling resulted in a total of 120 observation data. Data was collected from annual and sustainability reports from 68 state-owned enterprises on the Indonesia Stock Exchange (IDX) in 2019-2022. The data were processed and analyzed using WarpPLS 7.0 software. This research confirms that WBS can reduce the link between pressure and FSF and that pressure directly affects FSF. Any other variables cannot directly or indirectly influence financial statement fraud. The novelty of this research is the whistleblower system variable, which moderates the association between financial statement fraud and the factors of the fraud hexagon theory.